The Impact of Artificial Intelligence on Intellectual Capacities: Challenges and Implications - Ni Luh Regita Sumasningtyas; Ni Luh Putu Indriyani; I Made Joko Suryawan; Basilius Redan Werang (International Journal of Language and Literature, 2025)
There has been a decline in intellectual resilience, where individuals tend to give up quickly when faced with cognitive difficulties because they have become accustomed to receiving instant solutions from technology. The purpose of this study is to analyze the issues surrounding the use of AI and its impact on intellectual abilities. This research employed a literature review method. The research process involved several systematic steps.The identification and collection of sources began with searching for and gathering scholarly materials particularly national and international journal articles, that are highly relevant to the topic. The search was conducted using databases such as Google Scholar, ERIC, ScienceDirect, and Scopus for articles published between 2022 and 2025, resulting in 18 relevant articles that were then analyzed in depth. The findings indicate that the problems associated with AI use do not stem from the technology itself but from how humans utilize it. AI can produce positive impacts when used in a purposeful, critical, and creative manner; however, it may reduce intellectual capacity when it becomes an object of dependency. The study concludes that learning in the era of Artificial Intelligence must emphasize the strengthening of intellectual character, digital literacy, and ethical reasoning so that technological advancement aligns with the development of human cognitive maturity. The implication of this study is that teachers can utilize AI as a tool to facilitate learning, for example in personalizing materials or practice exercises, but strategies are still needed to ensure that students do not become entirely dependent on AI.